Pengaruh Kualitas Pelayanan Dan Citra Merek Terhadap Repurchase Intention Melalui Kepuasan Tamu Di Daima Gardenstay Padang - Azzahra.w, lathifa; Kahar, Azmen; Febrianto, Beni (Jurnal Ragam Pengabdian, 2026)
This study is intended to examine the effects of service quality and brand image on repurchase intention through guest satisfaction serving as a mediating variable among guests of Daima Gardenstay Padang. The study is motivated by a relatively high occupancy rate that is not matched by an adequate repeat guest percentage, along with online reviews that continue to highlight several service and facility aspects. A quantitative causal-associative approach was employed using a survey method. Purposive sampling was applied to select the study sample, yielding 160 respondents who had previously stayed at Daima Gardenstay Padang. Data were gathered through a 1-5 Likert-scale questionnaire and subsequently analyzed using two multiple linear regression models and the Sobel test to assess the mediating role of guest satisfaction. The findings revealed that service quality and brand image each exerted positive and significant effects on both guest satisfaction and repurchase intention. Guest satisfaction likewise had a positive and significant effect on repurchase intention, while the three variables simultaneously exerted a significant effect on repurchase intention (F = 51.509; R² = 0.498). The Sobel test results demonstrated that the effects of service quality (z = 3.446) and brand image (z = 3.645) on repurchase intention were partially mediated by guest satisfaction. These findings indicate that improving repurchase intention requires simultaneously strengthening service quality and brand image, with guest satisfaction serving as the key link between service experience and repurchase behavior